3D printed mechanochromic materials for visual signaling [data] - Kröger, Finn; Spiegel, Christoph A.; Blasco, Eva (Universität, 2025)
Mechanophores offer a unique approach to visualize stress via color change as a response to mechanical force. Their integration into polymeric materials has opened new pathways for real-time damage sensing and failure detection. When combined with additive manufacturing technologies, particularly high-resolution light-based 3D printing, mechanophore-based systems present great potential for developing functional materials with embedded signaling capabilities. In this work, we present new materials for digital light processing including spiropyran moieties as mechanophores. In particular, a spiropyran equipped with two photopolymerizable groups is synthesized and included into two printable formulations based on the monomers methyl acrylate and acrylic acid. The careful selection of the photoinitiator and crosslinker has enabled the 3D printing of complex 3D geometries, which visually respond to compression and tensile stress. The mechanochromic effect is demonstrated by the compression of a tube and a pad, which respond with a color change towards purple. Irradiation with Vis-light leads to a recovery in color and towards the shape before compression. Employing 3D printed “dog bones” as specimens, mechanochromic behavior is successfully demonstrated in response to tensile stress, initiating a similar change in color. Overall, the presented system shows great promise for creation of functional, high-resolution sensing 4D materials
Gefördert durch: Deutsche Forschungsgemeinschaft: SFB1249; Deutsche Forschungsgemeinschaft: „3D Matter Made to Order“ (EXC-2082/1-390761711); Carl Zeiss Foundation: Carl-Zeiss-Foundation-FocusHEiKA; Ministerium für Wissenschaft, Forschung und Kunst Baden-Württemberg (MWK): storage service SDS@hd; Deutsche Forschungsgemeinschaft: INST 35/1503-1 FUGG
Gesehen am 04.12.2025
Keywords: Forschungsdaten; Datenbank